Advantageous Comparison and Rationalization of Earnings Management - BROWN, TIMOTHY J. (Journal of Accounting Research, 2014)
ABSTRACT This paper proposes that psychological factors can change managers' beliefs about earnings management when they choose to engage in it. I show that, under certain circumstances, engaging in a small amount of earnings management alters a manager's beliefs about the appropriateness of the act, which may increase the likelihood of further earnings management. Specifically, I predict and find in two experiments that participants who initially choose to manage earnings are motivated to rationalize their behavior. Participants who are exposed to an egregious example of earnings management (commonly the focus of enforcement actions and press reports) have the opportunity to rationalize their behavior through a mechanism called “advantageous comparison,” where participants compare their behavior against the egregious example and conclude that what they did was relatively innocuous and appropriate. My analysis also indicates that presenting participants with an example of earnings management that is similar to the initial decision they made mitigates advantageous comparison. These results have implications for academics interested in how earnings management, and perhaps fraud, can accrete over time and for regulators and practitioners who are interested in preventing it.